CGI (Computer Generated Imagery) Technology in Anime Film “Ghost in the Shell” (Kokaku Kidotai) - Retno Mustikawati (Rekam: Jurnal Fotografi, Televisi, Animasi)
Ghost in the Shell is one of Japanese films, animation for this film is beautifully drawn and incorporates touches of CGI (Computer Generated Imagery) in representing the ‘net’, which exists analogously to the real world. CGI technology is not only used to attempt at creating convincing simulations of our reality, but also to create alternative realities. Today’s sophisticated (3D) CGI has been made possible by the development and combination of several techniques for simulating our visual reality. These techniques are constantly being refined and enhanced with new and more advanced simulation techniques, resulting in even more detailed representations. Computer generated imagery should not only be analyzed visually,but also ‘audiovisually’.